2015
DOI: 10.1017/mor.2015.32
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization and Performance of Chinese Family Firms: The Moderating Role of Corporate Governance

Abstract: This study investigates the differential effects of internationalization on two dimensions of family firms' performance: growth and profitability. Drawing on the contingency theory, we argue that the successful implementation of internationalization strategy requires an appropriate organization structure, which is usually absent in Chinese family firms. To the extent that such a structure is established, these firms can realize greater benefits from internationalization. From a sample of 225 family firms in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 86 publications
1
31
0
Order By: Relevance
“…Fourth, our research agenda calls for more research aimed at understanding the performance implications of internationalization and the role that governance‐, resource‐, and goal‐related characteristics of family firms have in determining internationalization outcomes. For instance, Lu, Liang, Shan, and Liang () found that while internationalization has a positive impact on growth, it has a negative impact on profitability, and the governance system of the family firm positively moderates the relationship between internationalization and profitability. What are the economic and noneconomic outcomes of the internationalization processes at the firm and subsidiary levels?…”
Section: Some Directions For Future Researchmentioning
confidence: 99%
“…Fourth, our research agenda calls for more research aimed at understanding the performance implications of internationalization and the role that governance‐, resource‐, and goal‐related characteristics of family firms have in determining internationalization outcomes. For instance, Lu, Liang, Shan, and Liang () found that while internationalization has a positive impact on growth, it has a negative impact on profitability, and the governance system of the family firm positively moderates the relationship between internationalization and profitability. What are the economic and noneconomic outcomes of the internationalization processes at the firm and subsidiary levels?…”
Section: Some Directions For Future Researchmentioning
confidence: 99%
“…Altindag et al (2011) found that entrepreneurial orientation has a direct and positive effect on firm growth while found that only innovativeness (one of the three dimensions of entrepreneurial orientation) has a positive and significant impact. Some scholars also identified internationalization as a meaningful driver of family business growth (Lu et al, 2015) where the need to pursue a global expansion is magnified by the ability of the family to recognize opportunities (Patel et al, 2012). However, entrepreneurial initiatives profoundly rooted in the local communities experience difficulties in expanding outside the local dimension: local embeddedness was indeed found to be an inhibitor of family business growth (Young and Cater, 2016).…”
Section: Business Antecedents and Outcomesmentioning
confidence: 99%
“…In the same vein, Casillas et al (2010) observe that the positive effect of proactiveness on firm growth is stronger in second‐generation firms than in first‐generation. Lu et al (2015) assert that a top management team dominated by family members negatively moderates the relationship between internationalization and firm growth due to the lack of expertise in the family talent pool. This line of thought is reinforced by Ward (1997), according to whom the ability to attract qualified non‐family managers is crucial to growth.…”
Section: Firm Growth In Family Firmsmentioning
confidence: 99%
“…In the studies of performance of family firms, the age of the firm has often been used as a control variable (Girma et al, 2004;Fryges and Wagner, 2010;Kneller and Pisu, 2010;Larimo, 2013;Kim and Gao, 2013;Cucculelli et al, 2014;Lu et al, 2015). However, several studies relate firm's age to strategic choices family firms pursue to improve their performance (Sorensen and Stuart, 2000;Jovanovic, 2001; Levesque and Minniti, 2006;Marshall et al, 2006;Minetti et al, 2015).…”
Section: Relevant Literaturementioning
confidence: 99%